(untitled) (The Nepali Mathematical Sciences Report, 2022)
In this article, we introduce and study a new class c0 (M, (X, ||.||), ā, ᾱ) of normed space (X, ||.||) valued difference sequences with the help of Orlicz function M . This is a generalization of the classical sequence space c0. Our primary interest is to explore some linear structures and investigate the conditions relating to the containment relation of the class c0 (M, (X, ||.||), ā, ᾱ) in terms of different ā and ᾱ.